Impact of Colombian yellow fruits and tropical fruits drinks consumption on the antioxidant status of healthy women (2016)
ABSTRACT: Reactive oxygen species are responsible for causing different types of damage in the body which are associated with the onset of chronic non-communicable diseases. A strategy to counteract these effects is by a diet rich in antioxidants compounds found in fruits. The aim of this study was to determine the antioxidant capacity in plasma and the content of total phenolic compounds in healthy women who consumed a drink prepared with Nativanox® Colombian tropical fruits or a drink prepared with Nativanox® Colombian yellow fruits during a short period of time. Nineteen healthy women received a daily 200 mL drink with Nativanox® Colombian tropical fruits or a drink with Nativanox® Colombian yellow fruits for 14 days. Before and after the intervention period blood and plasma were obtained to analyze C-reactive protein levels, lipid profile, total phenolic content and antioxidant status through FRAP, ABTS and EROS methods. Regular consumption of a drink with Nativanox® Colombian tropical fruits had a positive impact on the lipid profile and the antioxidant capacity on plasma of healthy women. The consumption of a drink with Nativanox® Colombian yellow fruits diminished diastolic blood pressure. These results showed that a Nativanox® Colombian yellow and tropical fruit contains bioactive compounds that can improve oxidative status in plasma and contribute to reduce the risk of cardiovascular disease.